First Record of a living Platycopida (Crustacea, Ostracoda) from Antarcticwaters and a Discussion on Cytherella serratula (Brady, 1880) - Brandão, Simone N. (Zootaxa, 2008)
Previous records of Platycopida (Ostracoda) from the Antarctic region of the Southern Ocean include only a few fossil species from the Late Cretaceous to the Palaeocene: Cytherelloidea megaspirocostata Majoran & Widmark, 1998, [sic] Cytherella serratula (Brady, 1880), plus seven species left in open nomenclature. The present study documents the first record of a living platycopid from the Antarctic region and describes Cytherella rwhatleyi sp. nov. as new. Comparison among specimens collected at stations 60° longitude and 10° of latitude apart from each other show that very little intraspecific variation in outline and ornamentation of the valves, as well as on the hemipenis is presented by this new species. Otherwise, clear differences on valve and hemipenis are observed between different species (herein, Jellinek & Swanson 2003). Review of the literature indicates that several species (with great differences in valve outline and ornamentation) have been erroneously assigned to Cytherella serratula (Brady, 1880) demonstrating that this so-called cosmopolitan taxon is in truth most probably restricted to bathyal depths of the Northwestern Atlantic. Finally, the abundances of Cytherella rwhatleyi sp. nov. in the samples studied herein (considering O2 concentration measurements) contradict the proposed relationship between Platycopida and O2 concentration in water masses (Whatley et al. 2003).